Effects of seven days’ fasting on physical performance and metabolic adaptation during exercise in humans - Kristoffer J. Kolnes; Emelie T. F. Nilsen; Steffen Brufladt; Allison M. Meadows; Per B. Jeppesen; Øyvind Skattebo; Egil I. Johansen; Jesper B. Birk; Kurt Højlund; Janne Hingst; Bjørn S. Skålhegg; Rasmus Kjøbsted; et al. (Nature Communications)
Abstract Humans have, throughout history, faced periods of starvation necessitating increased physical effort to gather food. To explore adaptations in muscle function, 13 participants (7 males and 6 females) fasted for seven days. They lost 4.6 ± 0.3 kg lean and 1.4 ± 0.1 kg fat mass. Maximal isometric and isokinetic strength remained unchanged, while peak oxygen uptake decreased by 13%. Muscle glycogen was halved, while expression of electron transport chain proteins was unchanged. Pyruvate dehydrogenase kinase 4 (PDK4) expression increased 13-fold, accompanied by inhibitory pyruvate dehydrogenase phosphorylation, reduced carbohydrate oxidation and decreased exercise endurance capacity. Fasting had no impact on 5’ AMP-activated protein kinase (AMPK) activity, challenging its proposed role in muscle protein degradation. The participants maintained muscle strength and oxidative enzymes in skeletal muscle during fasting but carbohydrate oxidation and high-intensity endurance capacity were reduced.